Dialectics at play: experiments with the Brechtian Learning Play (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
Reflections on a performance carried out by the Igreja Dialética Brechtiana project, having as object of analysis the proposition of a teaching and learning process of the dialectical thinking through theatrical play. The experience with two playful procedures was taken as material for the study. The game with the trial scene and the game of changing roles, placed in relation to the dialectical triad and the concept of dialectics at rest, and with tools from Bertolt Brecht’s learning plays, such as the interruption of the action and the displacement of the action from the stage to the audience. The conceptual reflection took place in dialogue with Walter Benjamin and Theodor W. Adorno, in addition to Brecht himself.
Keywords: theatrical game; dialectics; learning play; Bertolt Brecht; theater pedagogy